The nutritional impact of 7 versus 21 home-delivered medically tailored meals in patients with heart failure and malnutrition risk: a random order crossover feeding trial (MEDIMEALS) - Charlene Compher; Jule Anne Henstenburg; Marianne Aloupis; Amy Sun; Ryan Quinn; Elizabeth Emery; Jovina Thomas; Adrian Glass Crafford; Daniel R. Schwartz (BMC Nutrition)
Abstract Background Heart failure (HF) is frequently associated with malnutrition or malnutrition risk. The delivery of medically tailored meals (MTM) to the homes of patients with HF and malnutrition risk or malnutrition after hospital discharge holds promise for improving outcomes. However, the number of MTM needed to provide benefit is not established. Methods A random order crossover study was designed to compare the delivery of 7 versus 21 MTM for four weeks each to patients discharged from the hospital with HF and malnutrition risk. Telephone surveys were conducted at baseline, 30, and 60 days post-discharge to evaluate change in malnutrition risk, American Heart Association (AHA) diet goals, sarcopenia risk, and 30-day readmissions. Results Forty-six patients were enrolled. Patients had reduced odds of having malnutrition risk relative to the baseline score at one and two months (OR 0.18, 95% CI 0.04–0.74 and OR 0.21, 95% CI 0.05–0.99, respectively). The AHA diet score improved over time from baseline by 0.73 ± 0.22 units at one month (p = 0.0014), and by 0.48 ± 0.23 units at two months (p = 0.0430), regardless of the number of MTM provided. Sarcopenia risk improved over time (p = 0.01), decreasing by 0.43 ± 0.2 units by one (p = 0.03) and 0.59 ± 0.21 units by two months (p = 0.007) regardless of the number of MTM provided. Readmissions by 30 days were not significantly different based on the number of MTM provided (9% for 21 MTM vs 12.5% for 7 MTM), but well below national data at 23%. Conclusion The provision of at least seven MTM per week in the early window after hospital discharge to patients with HF and malnutrition or malnutrition risk is a promising strategy to improve malnutrition and sarcopenia risk and diet adherence, while keeping readmissions below national averages. Trial registration Clinicaltrials.gov NCT06142903, registered 11/23/2023.